2008
DOI: 10.1038/ki.2008.204
|View full text |Cite
|
Sign up to set email alerts
|

Telmisartan is more effective than losartan in reducing proteinuria in patients with diabetic nephropathy

Abstract: In patients with diabetic nephropathy, lowering blood pressure and reducing proteinuria by over 30% correlates with a slower progression to kidney failure. We compared two different angiotensin receptor-blockers in a double blind, prospective trial of 860 patients with type 2 diabetes whose blood pressure levels was over 130/80 mmHg or who were receiving antihypertensive medication(s) and who had a morning spot urinary protein to creatinine ratio of 700 or more. Patients were randomized to telmisartan (a highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
122
0
18

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(141 citation statements)
references
References 24 publications
1
122
0
18
Order By: Relevance
“…24 In this study, a more beneficial effect of telmisartan in reducing urinary protein excretion than losartan was accompanied by a more potent inhibitory effect of telmisartan on short-term BP variability and by its better lowering effect on nighttime systolic BP. Impaired diurnal autonomic nervous rhythm and proteinuria are closely related to the blunted decline in nocturnal BP and the resultant increase in nighttime BP, which is mainly caused by the comparative increase in sympathetic nerve activity.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…24 In this study, a more beneficial effect of telmisartan in reducing urinary protein excretion than losartan was accompanied by a more potent inhibitory effect of telmisartan on short-term BP variability and by its better lowering effect on nighttime systolic BP. Impaired diurnal autonomic nervous rhythm and proteinuria are closely related to the blunted decline in nocturnal BP and the resultant increase in nighttime BP, which is mainly caused by the comparative increase in sympathetic nerve activity.…”
Section: Discussionmentioning
confidence: 74%
“…Furthermore, previous studies have reported that telmisartan has a long-term half-life with peroxisome proliferator-activated receptor-g-activating property and a recent AMADEO study showed that telmisartan is superior to losartan in reducing proteinuria in hypertensive patients with diabetic nephropathy. 23,24 Therefore, in this study, we examined the possible effects of ARB losartan and telmisartan on diurnal BP profile, including the ambulatory short-term BP variability in hypertensive type II diabetic patients with overt nephropathy.…”
Section: Introductionmentioning
confidence: 99%
“…One such trial of 860 patients with type 2 diabetes, urinary protein ⁄ creatinine ratio (UACR) of 700, and hypertension found that telmisartan reduced UACR to a greater extent than losartan with no significant differences in BP after 52 weeks of therapy. 54 The authors speculated that this difference might be attributable to pharmacologic characteristics of the 2 drugs since telmisartan has a longer duration of action and is more lipophilic than losartan. left ventricular mass index has been complicated by differences in measurement techniques and criteria used in various clinical trials.…”
Section: Surrogate Markers Of CV Outcomes Proteinuriamentioning
confidence: 99%
“…In the AMADEO study, telmisartan was superior to losartan in reducing proteinuria in hypertensive patients with diabetic nephropathy despite a similar reduction in BP. 39 Masuda et al 40 reported that telmisartan reduced proteinuria and improved the ambulatory short-term BP variability in type 2 DM patients compared with losartan. However, Bahadir et al 41 reported that telmisartan and losartan had neutral effects on insulin resistance in hypertensive MetS patients.…”
Section: Discussionmentioning
confidence: 99%